Pengawasan Kesehatan Yustisial dan Peran RS Adhyaksa dalam Mencegah Penyalahgunaan Alasan Medis di Sistem Hukum Indonesia - Nurrakhmat, Adri (Pusat Strategi Kebijakan Penegakan Hukum, Kejaksaan Agung, 2025)
The misuse of health reasons by suspects or defendants in Indonesia's judicial system poses a significant challenge to the effectiveness of law enforcement. This study aims to analyze the impact of such misuse and evaluate the role of RS Adhyaksa as a judicial medical institution in ensuring transparency and fairness in the legal system. The research employs a qualitative approach using literature review and Open Source Intelligence (OSINT) to collect data from legal sources, academic journals, and real case studies. The findings indicate that without strict intervention and regulation, the misuse of health claims is projected to increase significantly by 2045, leading to prolonged legal processes and decreased public trust in the judiciary. Conversely, strengthening RS Adhyaksa’s role in verifying detainee health claims can reduce medical manipulation, enhance legal effectiveness, and optimize state budget allocations. The study concludes that reinforcing regulations and implementing technology in the judicial health system are crucial steps to ensuring a fair and transparent legal framework for the future.